REPRODUKSI MITOS DALAM TRADISI MANDI PADA MALAM JUMAT KLIWON DI SITUS BALEKAMBANG - Martanti, Nadia Luki; Brata, Nugroho Trisnu (Universitas Negeri Malang, 2024)
REPRODUCTION OF MYTHS IN THE TRADITION OF BATHING ON FRIDAY NIGHT KLIWON AT THE BALEKAMBANG SITEThe people of Sidorejo Village believe in the myth of Kliwon Friday night bathing at the Balekambang site. Myths that were previously feared by society are now being rearranged and updated to produce change. The purpose of writing the article is to analyse the process of commodification of the Balekambang Site myth being reproduced for the economic benefit of the community and to analyze the economic-social changes that have occurred in the Sidorejo Village community. The research method used is qualitative. The subjects of this research are the people at the Balekambang Site, Sidorejo Village. Data collection techniques in this research are observation, interviews, and documentation. The results of this research show that the reproduction process of the bathing myth on Kliwon Friday night is carried out by making the myth into a commodity, then distributing it by carrying out construction around the site. When taking a bath, which previously required burning offerings or incense, now you only need to say your wishes in your heart. The changes experienced by the community are related to increasingly diverse livelihoods and positive interactions to attract as many visitors as possible.Masyarakat Desa Sidorejo memiliki kepercayaan pada mitos mandi malam Jumat Kliwon di Situs Balekambang. Mitos yang dahulu ditakuti oleh masyarakat saat ini ditata kembali dan diperbaharui sehingga menghasilkan perubahan. Tujuan dari penulisan artikel untuk menganalisis proses komodifikasi mitos Situs Balekambang direproduksi untuk kepentingan ekonomi masyarakat dan mengalisisis perubahan ekonomi-sosial yang terjadi pada masyarakat Desa Sidorejo. Metode penelitian yang digunakan adalah metode kualitatif. Subjek penelitian ini adalah masyarakat di Situs Balekambang, Desa Sidorejo. Teknik pengumpulan data dalam penelitian ini adalah obersevasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukan bahwa proses reproduksi mitos mandi pada malam Jumat Kliwon dilakukan dengan menjadikan mitos sebagai komoditas, kemudian mendistribukannya dengan melakukan pembangunan di sekitar situs. Pelaksanaan mandi yang semula harus membakar sesaji atau dupa sekarang hanya perlu mengucapkan keinginan dalam hati saja. Adapun perubahan yang dialami masyarakat yaitu berkaitan dengan mata pencaharian yang semakin beragam dan interaksi yang positif untuk menarik pengunjung sebanyak-banyaknya.